2014
DOI: 10.15438/rr.4.3.76
|View full text |Cite
|
Sign up to set email alerts
|

Early Intraprosthetic Dislocation of Dual-Mobility Total Hip Arthroplasty Implant Following Attempted Closed Reduction: A Case Report

Abstract: Introduced in 1974 by Bousquet, the dual-mobility bearing for use in total hip arthroplasty (THA) confers increased jump distance and improved overall stability relative to conventional THA designs [1-3]. The dual-mobility bearing incorporates a relatively small (22-28mm) metal or ceramic femoral head press fit into a larger polyethylene liner which articulates with the acetabular component. Dissociation of the femoral head from the polyethylene liner (intraprosthetic dislocation) is a known late complication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In addition, it is important to note that the Morse taper is fully engaged with the head to avoid rim fatigue [22,55]. Recent articles have shown IPD for new DM designs in both short-and long-term series [41,[62][63][64], leading to implant failure. Interestingly, in these cases, the necks used were and generally of a large diameter.…”
Section: Intraprosthetic Dislocation As Results Of Pe Wearmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is important to note that the Morse taper is fully engaged with the head to avoid rim fatigue [22,55]. Recent articles have shown IPD for new DM designs in both short-and long-term series [41,[62][63][64], leading to implant failure. Interestingly, in these cases, the necks used were and generally of a large diameter.…”
Section: Intraprosthetic Dislocation As Results Of Pe Wearmentioning
confidence: 99%
“…Improved PE fabrication-besides the adoption of thinner and smoother trunnions, chamfered rims and eccentric centres of insert and shell rotation-have reduced this problem over the short [7,8] and medium [34,45,46] terms. Recent articles describe early failure of new DM designs in both short-and long-term series [41,[62][63][64]. Notably in these cases, necks used were and generally of a large diameter.…”
Section: Discussionmentioning
confidence: 99%
“…12 Missing this type of dislocation can result in acetabular component damage because the femoral head (metallic or ceramic) articulates directly with the smooth metallic shell, leading to acetabular damage that may necessitate shell revision. 13,14 Food and Drug Administration (FDA) approved trident acetabular shell in 2003, and the system is being widely used around with multiple liners. The shell is made of titanium with hydroxyapatite coating.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have highlighted that neck thickness and surface topography are important factors associated with poly wear of DM cups and play a role in the weakening of the retentive power of the poly liners ultimately leading to IPD of these bearing systems [7,8,[16][17][18][19]. Data on small numbers of retrievals is available [10,11,14,20], but there have been no attempts at quantifying the damage at the rim and at reporting when it is likely to occur in-vivo. In fact, as the majority of the studies addressing the issue of IPD report on gross deformation of the retentive rim only after dislocation, it is unknown whether it constitutes a gradual phenomenon that accumulates over time and finally results in the IPD episode or it is the result of an adverse event such as fibrosis or varus tilting of the liner culminating in the dislodgement of the head.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that the design of the femoral neck influences the stability of DM cups [10][11][12][13] but the mechanism is not known. This study explores the hypothesis that femoral stems with necks designed with smooth surfaces have less polyethylene rim deformation than necks designed with rough surfaces.…”
Section: Introductionmentioning
confidence: 99%